Self-expanding prestressed grouting material and preparation method thereof
By introducing self-stressed active materials of calcium carbide and aluminum carbide in the reinforcement of coal mine tunnel surrounding rocks, acetylene gas is generated to achieve expansion of grouting materials, solving the problem of lack of prestressed grouting materials in the prior art, and improving the stability and compressive strength of the tunnel surrounding rocks.
Patent Information
- Application Number
- CN202411945555.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The lack of prestressed grouting materials in the reinforcement of coal mine tunnel surrounding rocks has made it difficult to ensure the stability of tunnel surrounding rocks under external forces.
A self-expanding prestressed grouting material is proposed. By introducing self-stressed active materials of calcium carbide and aluminum carbide into the grouting material, it reacts with water to generate acetylene gas, and expanding the grouting material, thereby generating a prestressing effect.
This material promotes hydration and crystal nucleation of the gelled material by generating micro-nano bubbles, improves the compressive strength and seismic resistance of the grouting material, and enhances the stability of the surrounding rock in the tunnel.
Smart Images

Figure BDA0005214623870000071 
Figure BDA0005214623870000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of grouting material preparation, and in particular, the invention relates to a self-expanding prestressed grouting material and a preparation method thereof. Background Art
[0002] With the increase in the depth of coal mining, large deformation problems occur in the surrounding rock of coal mine tunnels. Grouting modification is an effective means of controlling the surrounding rock of tunnels, and has achieved good reinforcement effects. The concept of prestressed support refers to a technology that protects the stability of tunnels by resisting external forces by pre-applying stress. The core idea is to constrain the surrounding rock by applying a certain tension through prestressed anchors and grouting material systems before the surrounding rock of the tunnel is affected by external forces, so as to reduce its stress state and prevent the tunnel from being damaged. Prestressed support technology is widely used in tunnel support under various complex geological conditions, especially in difficult and complex tunnels with large sections, geological structure damage areas, weak and thick roofs, and high ground stress. At present, there are few reports on the research of prestressed grouting materials in grouting modification for tunnel surrounding rock reinforcement.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention proposes a self-expanding prestressed grouting material with a simple method, low cost and outstanding reinforcement effect and a preparation method thereof, and promotes its application.
[0005] On the one hand, an embodiment of the present invention provides a self-expanding prestressed grouting material, comprising the following components in parts by weight: 12-15 parts of self-stress active material, 1-2 parts of antioxidant, 1-2 parts of interface stabilizer, 1-2 parts of crystallization promoter, 1-3 parts of coagulant, 3-5 parts of reinforcing agent, and 100-120 parts of cementitious material.
[0006] In some embodiments, the self-stress active material is a mixture of calcium carbide and aluminum carbide;
[0007] Preferably, the mass ratio of the calcium carbide to the aluminum carbide is (4-6):1.
[0008] In some embodiments, the antioxidant is at least one of 2,6-di-tert-butylhydroquinone and 4-tert-butyl-5-methoxycatechol.
[0009] In some embodiments, the interfacial stabilizer is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid;
[0010] Preferably, the mass ratio of the triazine polycarboxylic acid triethanolamine salt to the polyoxyethylene lauryl ether carboxylic acid is 1:(1.5-3).
[0011] In some embodiments, the crystallization promoter is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex;
[0012] Preferably, the mass ratio of the triethylamine-borane complex to the zirconium dodecylbenzenesulfonate complex is 1:1.
[0013] In some embodiments, the coagulant is a mixture of lithium aluminum hydride and lithium chromate;
[0014] Preferably, the mass ratio of the lithium aluminum hydride to the lithium chromate is (2-3):1.
[0015] In some embodiments, the reinforcing agent is a mixture of methacrylic-cage polysilsesquioxane and acrylic-cage polysilsesquioxane;
[0016] Preferably, the mass ratio of the methacrylic cage-type silsesquioxane to the acrylic-cage-type polysilsesquioxane is 1:(2-4).
[0017] In some embodiments, the cementitious material is at least one of sulphoaluminate cement and aluminate cement.
[0018] Another aspect of the present invention is to provide a method for preparing the self-expanding prestressed grouting material, comprising the following steps:
[0019] S1, weighing a crystallization accelerator, a coagulant, a reinforcing agent and a gelling material respectively according to their weight fractions, and mixing them evenly to obtain a mixed material;
[0020] S2, weighing the self-stress active material, antioxidant, and interface stabilizer respectively according to their mass fractions, adding them to the mixed material, stirring and mixing, and obtaining the self-expanding prestressed grouting material.
[0021] In some embodiments, in step S2, the stirring and mixing time is 20 to 60 minutes.
[0022] The advantages and beneficial effects of the embodiments of the present invention are as follows:
[0023] (1) In the embodiment of the present invention, calcium carbide and aluminum carbide self-stress active materials are introduced into the grouting material. When the grouting material is added with water and stirred on site, the calcium carbide and aluminum carbide self-stress active materials react with water to generate acetylene gas, thereby causing the grouting material to expand and forming a prestress effect in the cracks, thereby effectively improving the grouting effect.
[0024] (2) The self-stressed active material in the embodiment of the present invention will generate a large number of micro-nano bubbles in the grouting material. These micro-nano bubbles act as heterogeneous crystal nuclei and serve as nucleation sites during the hydration process of the grouting material, which can promote the crystal nucleation and growth of the cementitious material, thereby improving the hydration degree of the grouting stone body and the compressive strength.
[0025] (3) The self-stress active material in the present invention will generate a large number of micro-nano bubbles in the grouting material, and the bubble phase and the solid phase will form a large number of solid-gas interfaces, which will increase the interface area of the grouting material system and significantly improve the interface energy. When the grouting structure is subjected to external impact, a large amount of impact energy is absorbed by the interface, so that the grouting material has better shock resistance and toughness resistance, and can be used stably under harsh tunnel impact.
[0026] (4) The embodiments of the present invention introduce calcium carbide and aluminum carbide self-stress active materials into the grouting material, which can react with water to generate a large amount of calcium hydroxide and aluminum hydroxide alkaline molecules. On the one hand, these alkaline molecules can combine with silicate ions in the cementitious material to form high-strength calcium silicate gel and aluminum silicate gel, thereby enhancing the compressive and tensile strength of the grouting material and improving its durability; on the other hand, these alkaline molecules can react with carbon dioxide in the air to produce a carbonization effect, thereby improving the mechanical strength of the grouting material. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0028] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0029] Herein, the words "comprises" and "includes" and variations thereof mean that other elements or integers which are permitted but not specifically described may be included.
[0030] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0031] On the one hand, an embodiment of the present invention provides a self-expanding prestressed grouting material, comprising the following components in parts by mass: 12-15 parts of self-stress active material (non-limiting examples: 12 parts, 13 parts, 14 parts, 15 parts, etc.), 1-2 parts of antioxidant (non-limiting examples: 1 part, 2 parts, etc.), 1-2 parts of interface stabilizer (non-limiting examples: 1 part, 2 parts, etc.), 1-2 parts of crystallization promoter (non-limiting examples: 1 part, 2 parts, etc.), 1-3 parts of coagulant (non-limiting examples: 1 part, 2 parts, etc.), 3-5 parts of reinforcing agent (non-limiting examples: 3 parts, 4 parts, 5 parts, etc.), 100-120 parts of cementitious material (non-limiting examples: 100 parts, 105 parts, 110 parts, 120 parts, etc.).
[0032] In some embodiments, the self-stress active material is a mixture of calcium carbide (CAS: 75-20-7) and aluminum carbide (CAS: 1299-86-1);
[0033] Preferably, the mass ratio of the calcium carbide to the aluminum carbide is (4-6):1, non-limiting examples include: 4:1, 5:1, 6:1, etc. The inventors have found through research that if the mass ratio of calcium carbide is too high, it will lead to excessive gas generation, thereby causing the mechanical properties of the grouting material to be lost; but if the mass ratio of calcium carbide is too low, it will lead to too little gas generation, low expansion ratio, and low prestress. Therefore, it is beneficial for the embodiment of the present invention to control the mass ratio of calcium carbide to aluminum carbide to (4-6):1.
[0034] In some embodiments, the antioxidant is at least one of 2,6-di-tert-butylhydroquinone (CAS: 2444-28-2) and 4-tert-butyl-5-methoxycatechol (CAS: 91352-66-8).
[0035] In some embodiments, the interface stabilizer is a mixture of triazine polycarboxylic acid triethanolamine salt (CAS: 80584-92-5) and polyoxyethylene lauryl ether carboxylic acid (CAS: 220622-96-8);
[0036] Preferably, the mass ratio of the triazine polycarboxylic acid triethanolamine salt to the polyoxyethylene lauryl ether carboxylic acid is 1:(1.5-3), non-limiting examples are: 1:1.5, 1:2, 1:3, etc.
[0037] By compounding triazine polycarboxylic acid triethanolamine salt with polyoxyethylene lauryl ether carboxylic acid as an interface stabilizer, microbubbles can be stably generated, so that the material has a better self-expansion effect. The inventors have found through research that if the amount of interface stabilizer added is too high, it will lead to the loss of overall mechanical properties of the grouting material; but if the amount of interface stabilizer added is too low, it will make it difficult for the generated microbubbles to exist stably, and the self-expansion effect will be weak. Therefore, the amount of interface stabilizer added in the embodiment of the present invention is controlled to be 1-2 parts.
[0038] In some embodiments, the crystallization promoter is a mixture of triethylamine-borane complex (CAS: 1722-26-5) and zirconium dodecylbenzenesulfonate complex (CAS: 109766-35-0);
[0039] Preferably, the mass ratio of the triethylamine-borane complex to the zirconium dodecylbenzenesulfonate complex is 1:1.
[0040] By compounding triethylamine-borane complex and dodecylbenzenesulfonic acid zirconium complex as crystallization promoter, the hydration crystallization of gelling material can be promoted. And the inventor found through research that if the addition amount of crystallization promoter is too high, the number of hydrated crystals produced will be large but small in size, and the impact resistance will be impaired; but if the addition amount of crystallization promoter is too low, the hydration crystallization effect will be weak and the mechanical strength will be low. Therefore, it is advantageous to control the addition amount of crystallization promoter to 1-2 parts in the embodiment of the present invention.
[0041] In some embodiments, the coagulant is a mixture of lithium aluminum hydride (CAS: 16853-85-3) and lithium chromate (CAS: 7789-01-7);
[0042] Preferably, the mass ratio of the lithium aluminum hydride to the lithium chromate is (2-3):1, non-limiting examples include: 2:1, 2.5:1, 3:1, etc.
[0043] By compounding lithium aluminum hydride and lithium chromate as a coagulant, the coagulation of the cementitious material can be promoted. The inventors have found through research that if the amount of the coagulant added is too high, the coagulation time will be short and the on-site operation window will be short; but if the amount of the coagulant added is too low, the coagulation effect will be poor and the coagulation will be slow. Therefore, the amount of the coagulant added in the embodiment of the present invention is controlled to be 1-3 parts.
[0044] In some embodiments, the reinforcing agent is a mixture of methacrylic cage-type silsesquioxane (CAS: 1204591-17-2) and acrylic-cage-type polysilsesquioxane (CAS: 1620202-27-8);
[0045] Preferably, the mass ratio of the methacrylic cage-type silsesquioxane to the acrylic-cage-type polysilsesquioxane is 1:(2-4), non-limiting examples are: 1:2, 1:3, 1:4, etc.
[0046] By compounding methacrylic cage-type silsesquioxane with acrylic-cage-type polysilsesquioxane as a reinforcing agent, the mechanical strength of the grouting material can be improved. The inventors have found through research that if the amount of the reinforcing agent added is too high, it will lead to poor dispersion, easily cause agglomeration, and damage the bending and impact resistance of the grouting material; but if the amount of the reinforcing agent added is too low, the reinforcing effect will be poor, and the mechanical strength of the grouting material will not be high. Therefore, the amount of the reinforcing agent added in the embodiment of the present invention is controlled to be 3-5 parts.
[0047] In some embodiments, the cementitious material is at least one of sulphoaluminate cement and aluminate cement.
[0048] Another aspect of the present invention is to provide a method for preparing the self-expanding prestressed grouting material, comprising the following steps:
[0049] S1, weighing a crystallization accelerator, a coagulant, a reinforcing agent and a gelling material respectively according to their weight fractions, and mixing them evenly to obtain a mixed material;
[0050] S2, weighing the self-stress active material, antioxidant, and interface stabilizer respectively according to their mass fractions, adding them to the mixed material, stirring and mixing, and obtaining the self-expanding prestressed grouting material.
[0051] In some embodiments, in step S2, the stirring and mixing time is 20 to 60 minutes, non-limiting examples include: 20 minutes, 30 minutes, 45 minutes, 50 minutes, 60 minutes, etc.
[0052] The technical solution of the present invention is further described in detail below in conjunction with specific examples. Unless otherwise specified, the various raw materials used in the examples are conventional commercial products or can be prepared by known methods.
[0053] Example 1
[0054] This embodiment provides a method for preparing a self-expanding prestressed grouting material, comprising the following steps:
[0055] S1, weigh 1 part of a crystallization accelerator, 1 part of a coagulant, 3 parts of a reinforcing agent and 100 parts of a gelling material respectively according to their mass parts, mix them evenly, and obtain a mixed material;
[0056] S2, weigh 12 parts of self-stress active material, 1 part of antioxidant, and 1 part of interface stabilizer respectively according to their mass parts, add them to the mixed material obtained in step S1, and stir and mix them in a dry powder mixer for 30 minutes to obtain a self-expanding prestressed grouting material.
[0057] The self-stress active material in this embodiment is a mixture of calcium carbide and aluminum carbide, and the mass ratio thereof is 5:1;
[0058] The antioxidant in this embodiment is 2,6-di-tert-butylhydroquinone;
[0059] The interface stabilizer in this embodiment is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid, and the mass ratio thereof is 1:2;
[0060] The crystallization accelerator in this embodiment is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex, and the mass ratio thereof is 1:1;
[0061] The coagulant in this embodiment is a mixture of lithium aluminum hydride and lithium chromate, and the mass ratio thereof is 2:1;
[0062] The reinforcing agent in this embodiment is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane, and the mass ratio thereof is 1:3;
[0063] The cementitious material in this embodiment is sulphoaluminate cement.
[0064] Example 2
[0065] This embodiment provides a method for preparing a self-expanding prestressed grouting material, comprising the following steps:
[0066] S1, weigh 2 parts of crystallization accelerator, 1 part of coagulant, 4 parts of reinforcing agent and 105 parts of gelling material respectively according to their mass parts, mix them evenly, and obtain a mixed material;
[0067] S2, weigh 13 parts of self-stress active material, 1 part of antioxidant, and 1 part of interface stabilizer respectively according to their mass parts, add them to the mixed material obtained in step S1, and stir and mix in a dry powder mixer for 30 minutes to obtain a self-expanding prestressed grouting material.
[0068] The self-stress active material in this embodiment is a mixture of calcium carbide and aluminum carbide, and the mass ratio thereof is 5:1;
[0069] The antioxidant in this embodiment is 4-tert-butyl-5-methoxycatechol;
[0070] The interface stabilizer in this embodiment is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid, and the mass ratio thereof is 1:2;
[0071] The crystallization accelerator in this embodiment is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex, and the mass ratio thereof is 1:1;
[0072] The coagulant in this embodiment is a mixture of lithium aluminum hydride and lithium chromate, and the mass ratio thereof is 2:1;
[0073] The reinforcing agent in this embodiment is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane, and the mass ratio thereof is 1:3;
[0074] The cementitious material in this embodiment is sulphoaluminate cement.
[0075] Example 3
[0076] This embodiment provides a method for preparing a self-expanding prestressed grouting material, comprising the following steps:
[0077] S1, weighing 1 part of a crystallization accelerator, 2 parts of a coagulant, 4 parts of a reinforcing agent and 110 parts of a gelling material respectively by weight, and mixing them evenly to obtain a mixed material;
[0078] S2, weigh 13 parts of self-stress active material, 2 parts of antioxidant, and 1 part of interface stabilizer respectively according to their mass parts, add them to the mixed material obtained in step S1, and stir and mix in a dry powder mixer for 30 minutes to obtain a self-expanding prestressed grouting material.
[0079] The self-stress active material in this embodiment is a mixture of calcium carbide and aluminum carbide, and the mass ratio thereof is 5:1;
[0080] The antioxidant in this embodiment is 2,6-di-tert-butylhydroquinone;
[0081] The interface stabilizer in this embodiment is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid, and the mass ratio thereof is 1:2;
[0082] The crystallization accelerator in this embodiment is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex, and the mass ratio thereof is 1:1;
[0083] The coagulant in this embodiment is a mixture of lithium aluminum hydride and lithium chromate, and the mass ratio thereof is 2:1;
[0084] The reinforcing agent in this embodiment is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane, and the mass ratio thereof is 1:3;
[0085] The cementitious material in this embodiment is aluminate cement.
[0086] Example 4
[0087] This embodiment provides a method for preparing a self-expanding prestressed grouting material, comprising the following steps:
[0088] S1, weigh 2 parts of crystallization accelerator, 2 parts of coagulant, 5 parts of reinforcing agent and 115 parts of gelling material respectively according to their mass parts, mix them evenly to obtain a mixed material;
[0089] S2, weigh 14 parts of self-stress active material, 1 part of antioxidant, and 1 part of interface stabilizer respectively according to their mass parts, add them to the mixed material obtained in step S1, and stir and mix in a dry powder mixer for 30 minutes to obtain a self-expanding prestressed grouting material.
[0090] The self-stress active material in this embodiment is a mixture of calcium carbide and aluminum carbide, and the mass ratio thereof is 5:1;
[0091] The antioxidant in this embodiment is 2,6-di-tert-butylhydroquinone;
[0092] The interface stabilizer in this embodiment is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid, and the mass ratio thereof is 1:2;
[0093] The crystallization accelerator in this embodiment is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex, and the mass ratio thereof is 1:1;
[0094] The coagulant in this embodiment is a mixture of lithium aluminum hydride and lithium chromate, and the mass ratio thereof is 2:1;
[0095] The reinforcing agent in this embodiment is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane, and the mass ratio thereof is 1:3;
[0096] The cementitious material in this embodiment is aluminate cement.
[0097] Example 5
[0098] This embodiment provides a method for preparing a self-expanding prestressed grouting material, comprising the following steps:
[0099] S1, weigh 2 parts of crystallization accelerator, 3 parts of coagulant, 5 parts of reinforcing agent and 120 parts of gelling material respectively according to their mass parts, mix them evenly, and obtain a mixed material;
[0100] S2, weigh 15 parts of self-stress active material, 2 parts of antioxidant, and 2 parts of interface stabilizer respectively according to their mass parts, add them to the mixed material obtained in step S1, and stir and mix them in a dry powder mixer for 30 minutes to obtain a self-expanding prestressed grouting material.
[0101] The self-stress active material in this embodiment is a mixture of calcium carbide and aluminum carbide, and the mass ratio thereof is 5:1;
[0102] The antioxidant in this embodiment is 4-tert-butyl-5-methoxycatechol;
[0103] The interface stabilizer in this embodiment is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid, and the mass ratio thereof is 1:2;
[0104] The crystallization accelerator in this embodiment is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex, and the mass ratio thereof is 1:1;
[0105] The coagulant in this embodiment is a mixture of lithium aluminum hydride and lithium chromate, and the mass ratio thereof is 2:1;
[0106] The reinforcing agent in this embodiment is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane, and the mass ratio thereof is 1:3;
[0107] The cementitious material in this embodiment is sulphoaluminate cement.
[0108] The performance of the grouting material prepared in the above embodiment was tested, and the results are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] As can be seen from Table 1, the embodiments of the present invention can produce a prestress effect by optimizing the formula composition of the grouting material and introducing calcium carbide and aluminum carbide self-stress active materials, which is beneficial to improving the grouting effect and can also improve the mechanical properties of the grouting material.
[0113] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0114] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A self-expanding prestressed grouting material, characterized in that: The invention comprises the following components in parts by weight: 12-15 parts of self-stress active material, 1-2 parts of antioxidant, 1-2 parts of interface stabilizer, 1-2 parts of crystallization promoter, 1-3 parts of coagulant, 3-5 parts of reinforcing agent and 100-120 parts of gelling material.
2. The self-expanding prestressed grouting material according to claim 1, characterized in that: The self-stress active material is a mixture of calcium carbide and aluminum carbide; Preferably, the mass ratio of the calcium carbide to the aluminum carbide is (4-6):
1.
3. The self-expanding prestressed grouting material according to claim 1, characterized in that: The antioxidant is at least one of 2,6-di-tert-butylhydroquinone and 4-tert-butyl-5-methoxycatechol.
4. The self-expanding prestressed grouting material according to claim 1, characterized in that: The interface stabilizer is a mixture of triazine polycarboxylic acid triethanolamine salt and polyoxyethylene lauryl ether carboxylic acid; Preferably, the mass ratio of the triazine polycarboxylic acid triethanolamine salt to the polyoxyethylene lauryl ether carboxylic acid is 1:(1.5-3).
5. The self-expanding prestressed grouting material according to claim 1, characterized in that: The crystallization accelerator is a mixture of triethylamine-borane complex and zirconium dodecylbenzenesulfonate complex; Preferably, the mass ratio of the triethylamine-borane complex to the zirconium dodecylbenzenesulfonate complex is 1:
1.
6. The self-expanding prestressed grouting material according to claim 1, characterized in that: The coagulant is a mixture of lithium aluminum hydride and lithium chromate; Preferably, the mass ratio of the lithium aluminum hydride to the lithium chromate is (2-3):
1.
7. The self-expanding prestressed grouting material according to claim 1, characterized in that: The reinforcing agent is a mixture of methacrylic cage-type silsesquioxane and acrylic-cage-type polysilsesquioxane; Preferably, the mass ratio of the methacrylic cage-type silsesquioxane to the acrylic-cage-type polysilsesquioxane is 1:(2-4).
8. The self-expanding prestressed grouting material according to claim 1, characterized in that: The cementitious material is at least one of sulphoaluminate cement and aluminate cement.
9. A method for preparing the self-expanding prestressed grouting material according to any one of claims 1 to 8, characterized in that: The steps include: S1, weighing a crystallization accelerator, a coagulant, a reinforcing agent and a gelling material respectively according to their weight fractions, and mixing them evenly to obtain a mixed material; S2, weighing the self-stress active material, antioxidant, and interface stabilizer respectively according to their mass fractions, adding them to the mixed material, stirring and mixing, and obtaining the self-expanding prestressed grouting material.
10. The method for preparing the self-expanding prestressed grouting material according to claim 9, characterized in that: In step S2, the stirring and mixing time is 20 to 60 minutes.
Citation Information
Patent Citations
Polyhedral oligomeric silsesquioxane modified composite grouting material suitable for low-permeability coal roadways and preparation method of polyhedral oligomeric silsesquioxane modified composite grouting material
CN117756493A
Performance-controllable inorganic grouting material as well as preparation method and application thereof
CN118239741A
Enhanced cement mixed with selected aggregates
US5378279A